2007
DOI: 10.2174/138527207779940892
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Warfare Agent Degradation and Decontamination

Abstract: The decontamination of chemical warfare agents (CWA) from structures, environmental media, and even personnel has become an area of particular interest in recent years due to increased homeland security concerns. In addition to terrorist attacks, scenarios such as accidental releases of CWA from U.S. stockpile sites or from historic, buried munitions are also subjects for response planning. To facilitate rapid identification of practical and effective decontamination approaches, this paper reviews pathways of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 21 publications
0
72
0
Order By: Relevance
“…These permeation values represent a vapor molar selectivity for H 2 O/2-chloroethyl ethyl sulfide of 150, which is 500 times higher than the H 2 O/2-chloroethyl ethyl sulfide selectivity seen through pure, vulcanized BR on the same support. 35 This same Q I -phase cross-linked 3b/BR/H 2 O polymer material was later examined as a breathable barrier for protection against nerve agent CWAs (that is, highly toxic, reactive organophosphorus esters that disrupt neurochemical pathways and cause the loss of autonomic functions 36 ). 38 Using dimethyl methylphosphonate (DMMP) as a nerve agent simulant, it was found that the cross-linked, Q I -phase 3b/BR/H 2 O composite worked extraordinarily well for the rejection of DMMP while maintaining high water-vapor breathability.…”
Section: Design and Development Of Directly Cross-linked Q-phase Llc mentioning
confidence: 99%
“…These permeation values represent a vapor molar selectivity for H 2 O/2-chloroethyl ethyl sulfide of 150, which is 500 times higher than the H 2 O/2-chloroethyl ethyl sulfide selectivity seen through pure, vulcanized BR on the same support. 35 This same Q I -phase cross-linked 3b/BR/H 2 O polymer material was later examined as a breathable barrier for protection against nerve agent CWAs (that is, highly toxic, reactive organophosphorus esters that disrupt neurochemical pathways and cause the loss of autonomic functions 36 ). 38 Using dimethyl methylphosphonate (DMMP) as a nerve agent simulant, it was found that the cross-linked, Q I -phase 3b/BR/H 2 O composite worked extraordinarily well for the rejection of DMMP while maintaining high water-vapor breathability.…”
Section: Design and Development Of Directly Cross-linked Q-phase Llc mentioning
confidence: 99%
“…The reaction mechanism is similar to as given in Figs 8 to 11. 7.27 Nanosized Metal Oxides as CWA Decontaminants Recently, nanosized particles of MgO, Al 2 O 3 and CaO have been found to be the potential reactive sorbent materials owing to their high surface area, strong adsorbability, potential reactivity towards chemical warfare agents, and these remove the agent rapidly from the contaminated surfaces and degrade them in situ and render the hazardous agents non-toxic [32][33][34][35][36][37][38] . In addition, titania nanotubes, manganese oxide nanotubes were also found to be having promising CWA decontamination properties [76][77][78][79][80] .…”
Section: Peroxybicarbonate-based Formulationsmentioning
confidence: 99%
“…The development has been concentrated on the physical protection of body and respiration, medical protection involving pretreatment and therapy, and detection for alarming, monitoring, identification, and verification of CWA [3] but also on the efficient decontamination of contaminated skin, equipment, vehicles, land areas, and other surfaces [132,133]. Furthermore, the CWC obligates that existing CWA stockpiles and production facilities are destroyed, so those States Parties owing large stocks of CWAs have needed methods for efficient dispose of munitions.…”
Section: Degradation In Detoxification Solutionsmentioning
confidence: 99%